Fixed Point Theorem With The CLR's Property and OWC Mappings in Menger Space - Satyanna, K.; Srinvas, V. (Communications in Mathematics and Applications, 2021)
In this paper, we prove a fixed point theorem in Menger space by employing the conditions CLR's-property and occasionally weakly compatible mappings, which generalizes the theorem proved by Malviya et al. [5]. Further, this result is justified by a suitable example.
Keywords: CLRs-property; Occasionally weakly compatible mappings; Menger space